Preparation for top-up operation at Diamond - Walker, R; Bartolini, R; Bonner, P; Burge, F; Chernousko, Y; Christou, C; Dobbing, J; Heron, M; Kempson, VC; Martin, I; Rehm, G; Rushton, R; et al. (European Physical Society Accelerator Group (EPS-AG), 2008)
It is planned to start top-up operation in Diamond in the near future. In this report we summarise the various activities that have led up to this point, including radiation safety considerations, preparation of hardware interlocks and control software, and injection optimisation.